2022
DOI: 10.3389/fenvs.2022.955121
|View full text |Cite
|
Sign up to set email alerts
|

Green economic development under the fiscal decentralization system: Evidence from china

Abstract: The literature is still divided on the study of the ecological and economic effects of fiscal decentralization. To clarify the relationship between fiscal decentralization between central and local governments and green economic development in developing countries, we take China as an example to test the impact of fiscal decentralization on green total factor productivity and its mechanism. It is found that fiscal decentralization helps local governments play a greater role in the regional economic system and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 31 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…The research on fiscal decentralization is mainly empirical, primarily focusing on two dimensions of economic and environmental governance. In terms of the impact of fiscal decentralization on the economy, Wang et al [5] found that fiscal decentralization will promote the development of green economy and promote the role of local governments in regional economic development. Yi [6] found that fiscal decentralization has a positive spatial spillover effect on green technology innovation and also promotes the surrounding areas.…”
Section: Literature Review 21 Research On Fiscal Decentralizationmentioning
confidence: 99%
“…The research on fiscal decentralization is mainly empirical, primarily focusing on two dimensions of economic and environmental governance. In terms of the impact of fiscal decentralization on the economy, Wang et al [5] found that fiscal decentralization will promote the development of green economy and promote the role of local governments in regional economic development. Yi [6] found that fiscal decentralization has a positive spatial spillover effect on green technology innovation and also promotes the surrounding areas.…”
Section: Literature Review 21 Research On Fiscal Decentralizationmentioning
confidence: 99%
“…The empirical model includes provincial level fixed effects to control for the time-invariant provincial characteristics or cross-province heterogeneity, and year fixed effects to control for national shocks and policy changes that are common to all provinces in a given year. Conversely, a lower fiscal sufficiency rate denotes the greater reliance of the region on intergovernmental fiscal transfer payments (Yang, 2014). However, our study provides empirical evidence that local governments' fiscal self-sufficiency is not a key factor to help local governments maintain long-term debt sustainability.…”
Section: Estimation Strategymentioning
confidence: 69%
“…Song et al [29], Feng et al [30], and Yu et al [31] suggest that optimizing resource allocation, improving local public infrastructure, stimulating enterprise innovation, and promoting the green development of the economy can be achieved through fiscal decentralization. Wang et al [32] found that fiscal decentralization promotes competitiveness among local governments in technological innovation and other sectors, leading to an enhancement in green total factor productivity. They accomplished this by utilizing provincial data to construct a panel model for empirical analysis.…”
Section: Literature Reviewmentioning
confidence: 99%